2011
DOI: 10.1186/1471-2407-11-423
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of epidermal growth factor receptor targeting in advanced chordoma: case report and literature review

Abstract: BackgroundChordomas are very rare low-grade malignant bone tumors that arise from the embryonic rests of the notochord. They are characterized by slow growth and long history with frequent local relapses, and sometimes metastases. While chemotherapy is not efficient, imatinib has shown antitumor activity.Case presentationWe report on a 76-year-old patient with EGFR-overexpressing advanced chordoma that progressed on imatinib and subsequently responded to erlotinib during 12 months.ConclusionsWe report the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…Shalaby et al (62) demonstrated that ErbB1 inhibitor tyrosine (AG1487) markedly inhibited proliferation of the chordoma cell line U-CH1 in vitro and diminished ErbB1 phosphorylation, and these data implicated aberrant ErbB1 signaling in the pathogenesis of chordomas. Furthermore, four clinical cases highlighted the antitumor activity of ErbB1 inhibition in advanced chordomas (68)(69)(70)(71). These studies support the conclusion that ErbB1 could be a potential target for improving treatment of osteosarcomas.…”
Section: Erbb Receptors In Chordomamentioning
confidence: 53%
“…Shalaby et al (62) demonstrated that ErbB1 inhibitor tyrosine (AG1487) markedly inhibited proliferation of the chordoma cell line U-CH1 in vitro and diminished ErbB1 phosphorylation, and these data implicated aberrant ErbB1 signaling in the pathogenesis of chordomas. Furthermore, four clinical cases highlighted the antitumor activity of ErbB1 inhibition in advanced chordomas (68)(69)(70)(71). These studies support the conclusion that ErbB1 could be a potential target for improving treatment of osteosarcomas.…”
Section: Erbb Receptors In Chordomamentioning
confidence: 53%
“…[44] Two cases of treatment with an alternative EGFR inhibitor, erlotinib, also showed significant response. [4281] The successes seen with these EGFR inhibitors suggest that targeting EGFR in chordoma is an effective method of treatment that should be incorporated into the arsenal of therapies available for chordoma patients.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Most of these drugs have shown modest activity in case reports and case series, administered either as monotherapy or combined with other agents [713]. A dedicated phase 2 study of lapatinib in EGFR-positive chordoma resulted in a progression free survival (PFS) of 8 months [14].…”
Section: Introductionmentioning
confidence: 99%